(untitled) (Research, Society and Development, 2021)
This is an experience report article that aimed to describe the acting of the psychologistin a Psychosocial Care Center for children and adolescents in the city of Florianópolis (SC). The experience came from an experience by students in a theoretical-practical activity of a discipline of the Undergraduate Course in Psychology at the University of the South of Santa Catarina in the second semester of 2019. A project was carried out to learn about the service and the acting of the psychologist. The result reflected the professional training and the ethics of the desire to strengthen the clinic and politics in daily work. It is concluded that the psychologist’s acting in this service goes through the specific competences recommended by the legislation of professional practice, the guidelines of the Psychosocial Care Network, a code of ethics from the moment that each demand and context requires a reinvention of the psychologist’s acting.